BIDASARI : Jewel of Malay Muslim culture - Millie, Julian, 1967- (Bibliotheca Indonesic, 2004)
The sly wit and silky eroticism of the verse genre known as romantic syair were staple dishes on the Southeast Asian cultural menu, especially in the Malay, Islamic regional centres. Yet very few examples are available in translation for the many readers interested in the genre, and attempts by academics to account for their powers of attraction are even rarer. This book is the author s effort to convey the seductive qualities of the sexiest of the romantic syair, the Poem of Bidasari . Few Malay works have been loved and disseminated to the extent the Syair Bidasari has. It was translated in other languages of the region like Makassarese and Maranao and adapted for the Malay theatre and cinema. Three tasks are attempted in the book: a transliteration into Roman characters of one of the surviving Malay manuscripts of the poem, a translation of that manuscript into English, and an inquiry into the poem s virtues. The intertexts drawn upon in the analysis reveal the author s conviction that understanding of traditions of kesenian rakyat (popular arts) such as pantun and the Malay theatre provides the background that allows the text to signify most powerfully.